The Use of Scientific Literacy-Based Sound Wave E-Worksheets to Improve Students’ Scientific Literacy Skills in Online Physics Learning - Lestari, Putri Cahya; Miriam, Sarah; Misbah, Misbah (Universitas Islam Negeri Raden Intan Lampung, 2026)
Scientific literacy is a key competency in physics learning because it enables students to explain phenomena, evaluate evidence, apply mathematical reasoning, and connect scientific concepts with everyday contexts. However, developing this competency remains challenging in online science learning, particularly when students have limited opportunities for guided inquiry and evidence-based activities. This study aimed to examine the effectiveness of a scientific literacy-based sound wave e-worksheet in improving eleventh-grade students’ scientific literacy during online physics learning. The study employed the implementation and evaluation stages of an ADDIE-based research and development design with a one-group pretest–posttest approach. The participants were 15 eleventh-grade students at a public senior high school in Banjarbaru City, Indonesia. Data were collected using a scientific literacy test covering six indicators: explaining scientific phenomena, identifying scientific questions, solving everyday problems using mathematical reasoning, identifying experimental variables, using scientific evidence to draw conclusions, and applying scientific conclusions in daily life. The data were analyzed using descriptive statistics and normalized gain. The results showed that students’ mean scientific literacy score increased from 22.87, categorized as poor, to 65.91, categorized as good, with an overall N-Gain of 0.56, indicating moderate improvement. High gains were found in identifying scientific questions, mathematical reasoning, and identifying experimental variables, whereas explaining scientific phenomena showed the lowest gain. These findings indicate that the e-worksheet is feasible for supporting procedural and quantitative aspects of scientific literacy in online physics learning, although stronger scaffolding is needed to improve conceptual explanation and contextual application.